Status Report. Participatory Rangeland Management (PRM) Sites in Baringo, Kenya 2022 - International Livestock Research Institute (International Livestock Research Institute, 2022)
Between December 2017 and December 2021, the EU-funded Piloting of Participatory Rangeland Management (PRM) project in Kenya supported two community conservancies: one community forest association and one community rangeland initiative to carry out community resource mapping, rangeland resource rehabilitation, protection and management leading to the rehabilitation of 89,000 hectares of land, one borehole, one spring, and strengthening four community management committees. This was implemented in Mogotio Subcounty (Koitegan), Tiaty (Paka Hills), Marigat (Irong Conservancy), and Baringo North (Kabarion Conservancy). Now this work will be taken up, improved and scaled up under the CGIAR initiative Livestock and Climate (LCSR). This report provides the status of the current sites in order to identify the next steps, interventions and supporting research and technical support. The new phase will focus on scaling up and scaling out the PRM project in Baringo and Wajir counties